Characterization of β-Ti alloy prepared by SLM method - Vonavkova, Ilona; Vojtech, Dalibor; Palousek, David (Manufacturing Technology Journal, 2020)
Ti-6Al-4V alloy is the most commercially used material for the production of orthopedic implants. However, despite its excellent properties, it is not an ideal material for use in medicine in terms of vanadium toxicity and relatively high modulus of elasticity. Titanium β-alloys could be a suitable replacement in future years for Ti-6Al-4V alloy, as they have a lower modulus of elasticity and contain non-toxic elements. Some of the alloying elements may even increase the biocompatibility of the alloy. In addition, a progressive 3D printing method would allow custom-made implants with the required properties to be printed. The aim of this work was to characterize the β alloy Ti-30Nb by Selective Laser Melting (SLM) method and to determine its mechanical properties. In addition, heat treatment was applied in order to homogenize the structure. Ti-30Nb alloy was compared in as-built state and in annealed state.
Keywords: Titanium alloy; Ti-Nb; 3D printing; SLM